Electronic Brains: Stories from the Dawn of the Computer Age - Mike Hally (The National Academies Press, 2005)
We've come so far, so fast. Within a relatively short period of time, we've managed to put enormous computing power in offices and homes around the globe. But before there was an IBM computer, before there were laptops and personal PCs, there were small independent teams of pioneers working on the development of the very first computer. Scattered around the globe and ranging in temperament and talent, they forged the future in basement labs, backyard, workshops, and old horse barns. Tracing the period just after World War II when the first truly modern computers were developed, Electronic Brains chronicles the escapades of the world's first "techies." Some of the initial projects are quite famous and well known, such as "LEO", the Lyons Electronic Office, which was developed by the catering company J. Lyons & Co. in London in the 1940s. Others are a bit more arcane, such as the ABC, which was built in a basement at Iowa State College and was abandoned to obscurity at the beginning of WWII. And then - like the tale of the Rand 409 which wss constructed in a barn in Connecticut under the watchful eye of a stuffed moose - there are the stories that are virtually unknown. All combine to create a fascinating history of a now-ubiquitous technology. Relying on extensive interviews from surviving members of the original teams of hardware jockeys, author Mike Hally recreates the atmosphere of the early days of computing. Rich with provocative and entertaining descriptions, we are introduced go the many eccentric, obsessive, and fiercely loyal men and women who laid the foundations for the computerized world in which we now live. As the acronyms fly fast and furious - UNIVAC, CSIRAC, and MESM, to name just a few - Electronic Brains provides a vivid sense of time, place, and science.
Keywords: Explore Science; Computers and Information Technology

Cord Blood: Establishing a National Hematopoietic Stem Cell Bank Program - Institute of Medicine (The National Academies Press, 2005)
With the potential for self-renewal and differentiation, the possibilities for stem cells are enormous. One specific type of stem cell, the hematopoietic progenitor cell (HPC), which is derived from umbilical cord blood (as well as adult bone marrow and mobilized peripheral blood), holds particular promise. To make the most of these HPCs, the Institute of Medicine was asked to consider the optimal structure for a national cord blood program and to address pertinent issues related to maximizing the potential of stem cell technology. Cord Blood: Establishing a National Hematopoietic Stem Cell Bank Program examines: The role of cord blood in stem cell transplantation The current status of blood banks already in existence The optimal structure for the cord blood program The current use and utility of cord blood for stem cell transplants The best way to advance the use of cord blood units and make them available for research Expert advice from leaders in the fields of economics, public health, medicine, and biostatistics combine to make this very timely and topical book useful to a number of stakeholders.
Keywords: Health and Medicine

Guidelines for Human Embryonic Stem Cell Research - Institute of Medicine; National Research Council (The National Academies Press, 2005)
Since 1998, the volume of research being conducted using human embryonic stem (hES) cells has expanded primarily using private funds because of restrictions on the use of federal funds for such research. Given limited federal involvement, privately funded hES cell research has thus far been carried out under a patchwork of existing regulations, many of which were not designed with this research specifically in mind. In addition, hES cell research touches on many ethical, legal, scientific, and policy issues that are of concern to the public. This report provides guidelines for the conduct of hES cell research to address both ethical and scientific concerns. The guidelines are intended to enhance the integrity of privately funded hES cell research by encouraging responsible practices in the conduct of that research.
Keywords: Health and Medicine

Re-Engineering Water Storage in the Everglades: Risks and Opportunities - National Research Council (The National Academies Press, 2005)
The Water Science and Technology Board and the Board on Environmental Studies and Toxicology have released the seventh and final report of the Committee on Restoration of the Greater Everglades Ecosystem, which provides consensus advice to the South Florida Ecosystem Restoration Task Force on various scientific and technical topics. Human settlements and flood-control structures have significantly reduced the Everglades, which once encompassed over three million acres of slow-moving water enriched by a diverse biota. To remedy the degradation of the Everglades, a comprehensive Everglades Restoration Plan was formulated in 1999 with the goal of restoring the original hydrologic conditions of its remaining natural ecosystem. A major feature of this plan is providing enough storage capacity to meet human needs while also providing the needs of the greater Everglades ecosystem. This report reviews and evaluates not only storage options included in the Restoration Plan but also other options not considered in the Plan. Along with providing hydrologic and ecological analyses of the size, location and functioning of water storage components, the report also discusses and makes recommendations on related critical factors, such as timing of land acquisition, intermediate states of restoration, and tradeoffs among competing goals and ecosystem objectives.
Keywords: Earth Sciences; Environment and Environmental Studies

Building an Electronic Records Archive at the National Archives and Records Administration: Recommendations for a Long-Term Strategy - National Research Council (The National Academies Press, 2005)
The federal government generates and increasingly saves a large and growing fraction of its records in electronic form. In 1998, the National Archives and Record Administration (NARA) launched its Electronic Archives (ERA) program to create a system to preserve and provide access to federal electronic records. To assist in this project, NARA asked the NRC to conduct a two-phase study to provide advice as it develops the ERA program. The first two reports (phase one) provided recommendations on design, engineering, and related issues facing the program. This report (phase two) focuses on longer term, more strategic issues including technology trends that will shape the ERA system, archival processes of the ERA, and future evolution of the system. It also provides an assessment of technical and design issues associated with record integrity and authenticity.
Keywords: Computers and Information Technology

An International Spent Nuclear Fuel Storage Facility: Exploring a Russian Site as a Prototype: Proceedings of an International Workshop - National Research Council (The National Academies Press, 2005)
As part of a long-standing collaboration on nuclear nonproliferation, the National Academy of Sciences and the Russian Academy of Sciences held a joint workshop in Moscow in 2003 on the scientific aspects of an international radioactive disposal site in Russia. The passage of Russian laws permitting the importation and storage of high-level radioactive material (primarily spent nuclear fuel from reactors) has engendered interest from a number of foreign governments, including the U.S., in exploring the possibility of transferring material to Russia on a temporary or permanent basis. The workshop focused on the environmental aspects of the general location and characteristics of a possible storage site, transportation to and within the site, containers for transportation and storage, inventory and accountability, audits and inspections, and handling technologies.
Keywords: Environment and Environmental Studies

The Smallpox Vaccination Program: Public Health in an Age of Terrorism - Institute of Medicine (The National Academies Press, 2005)
December 13, 2002, the president of the United States announced that smallpox vaccination would be offered to some categories of civilians and administered to members of the military and government representatives in high-risk areas of the world. The events that precipitated that historic announcement included a series of terrorist attacks during the 1990s, which culminated in the catastrophic events of 2001. Although preparedness for deliberate attacks with biologic weapons was already the subject of much public health planning, meetings, and publications as the twentieth century neared its end, the events of 2001 led to a steep rise in bioterrorism-related government policies and funding, and in state and local preparedness activities, for example, in public health, health care, and the emergency response and public safety communities. The national smallpox vaccination program is but one of many efforts to improve readiness to respond to deliberate releases of biologic agents. The Institute of Medicine (IOM) Committee on Smallpox Vaccination Program Implementation was convened in October 2002 at the request of the Centers for Disease Control and Prevention (CDC), the federal agency charged with implementing the government's policy of providing smallpox vaccine first to public health and health care workers on response teams, then to all interested health care workers and other first responders, and finally to members of the general public who might insist on receiving the vaccine. The committee was charged with providing "advice to the CDC and the program investigators on selected aspects of the smallpox program implementation and evaluation." The committee met six times over 19 months and wrote a series of brief "letter" reports. The Smallpox Vaccination Program: Public Health in an Age of Terrorism constitutes the committee's seventh and final report, and the committee hopes that it will fulfill three purposes: 1) To serve as an archival document that brings together the six reports addressed to Julie Gerberding, director of CDC, and previously released on line and as short, unbound papers; 2) To serve as a historical document that summarizes milestones in the smallpox vaccination program, and ; 3) To comment on the achievement of overall goals of the smallpox vaccination program (in accordance with the last item in the charge), including lessons learned from the program.
Keywords: Conflict and Security Issues; Health and Medicine

Climate Crash: Abrupt Climate Change and What It Means for Our Future - John D. Cox (The National Academies Press, 2005)
As scientists carefully search for clues in the sun and storm patterns from our distant past, they are gradually writing a new history of Earth's climate. Layers extracted from cores drilled into glaciers and ice sheets, sediments collected from the shores of lakes and oceans, and growth rings exposed in ancient corals and trees all tell the same surprising story. It is now apparent that alterations in our climate can happen quickly and dramatically. Physical evidence reveals that centuries of slow, creeping climate variations have actually been punctuated by far more rapid changes. While this new paradigm represents a significant shift in our picture of Earth's past, the real question is what it means for our future. Many researchers are now quietly abandoning the traditional vision of a long, slow waltz of slumbering ice ages and more temperate periods of interglacial warming. While they've long recognized the threats posed by global warming, they must now consider that the natural behavior of our climate is perhaps a greater threat than we'd imagined. And though there is no need for immediate alarm, the fact that changes in our climate can happen much more quickly than we'd originally thought--perhaps in the course of a human lifetime--makes it clear that science has a lot of questions to answer in this area. What are the mechanisms for triggering a significant climate change? In what ways should we expect this change to manifest itself? When will it likely happen? Climate Crash seeks to answer these questions, breaking the story of rapid climate change to a general public that is already intensely curious about what science has to say on the topic.
Keywords: Explore Science; Earth Sciences

Review of the HIVNET 012 Perinatal HIV Prevention Study - Institute of Medicine (The National Academies Press, 2005)
Mother-to-child transmission of HIV-1 afflicts hundreds of thousands of children every year, especially in parts of the world such as sub-Saharan Africa, where HIV infection is prevalent and resources are limited. This tragic reality has spurred researchers to search for an effective, safe, and inexpensive treatment that could reduce the risk of perinatal HIV transmission. The HIVNET 012 trial was designed to provide preliminary information on the comparative safety and efficacy of two relatively simple and inexpensive short courses of oral antiretroviral treatment likely to be feasible in resource-limited settings. The resulting report identified some problems with procedures and documentation, but concluded that these issues did not compromise the results of the study. However, these issues have led to public scrutiny and continued controversy. Review of the HIVNET 012 Perinatal HIV Prevention Study critically and objectively evaluates the study's design and conduct, and assesses the impact of the initial procedural issues on the validity of the overall findings and conclusions of the trial.
Keywords: Health and Medicine

Tank Wastes Planned for On-Site Disposal at Three Department of Energy Sites: The Savannah River Site: Interim Report - National Research Council (The National Academies Press, 2005)
In response to a request from Congress, the U.S. Department of Energy (DOE) asked the National Academies to evaluate its plans for managing radioactive wastes from spent nuclear fuel at sites in Idaho, South Carolina, and Washington. This interim report evaluates storage facilities at the Savannah River Site in South Carolina, with a particular focus on plans to seal the tanks with grouting. The report finds that tanks at the site do not necessarily need to be sealed shut as soon as the bulk of the waste has been removed. Postponing permanent closure buys more time for the development and application of emerging technologies to remove and better immobilize residual waste, without increasing risks to the environment or delaying final closure of the "tank farms." The report also recommends alternatives to address the lack of tank space at the site, as well as the need for focused R&D activities to reduce the amount and improve the immobilization of residual waste in the tanks and to test some of the assumptions used in evaulating long-term risks at the site.
Keywords: Environment and Environmental Studies

Touch the Sun: A NASA Braille Book - Noreen Grice (The National Academies Press, 2005)
Touch the Sun is a universally designed book with colorful raised images and combined text in print and Braille that explores the dynamic nature of our Sun. Topics include: size comparison between Earth and the Sun, the interior layers of the Sun, sunspots and their motion, views of the Sun in visible and ultraviolet light, solar eruptions as seen from space based observatories, massive solar storms, and the effect of space weather on Earth. According to the author, "This book is hot!"
Keywords: Space and Aeronautics

Wormwood Forest: A Natural History of Chernobyl - Mary Mycio (The National Academies Press, 2005)
When a titanic explosion ripped through the Number Four reactor at the Chernobyl Nuclear Plant in 1986, spewing flames and chunks of burning, radioactive material into the atmosphere, one of our worst nightmares came true. As the news gradually seeped out of the USSR and the extent of the disaster was realized, it became clear how horribly wrong things had gone. Dozens died - two from the explosion and many more from radiation illness during the following months - while scores of additional victims came down with acute radiation sickness. Hundreds of thousands were evacuated from the most contaminated areas. The prognosis for Chernobyl and its environs - succinctly dubbed the Zone of Alienation - was grim. Today, 20 years after the worst nuclear power plant accident in history, intrepid journalist Mary Mycio dons dosimeter and camouflage protective gear to explore the world's most infamous radioactive wilderness. As she tours the Zone to report on the disaster's long-term effects on its human, faunal, and floral inhabitants, she meets pockets of defiant local residents who have remained behind to survive and make a life in the Zone. And she is shocked to discover that the area surrounding Chernobyl has become Europe's largest wildlife sanctuary, a flourishing - at times unearthly - wilderness teeming with large animals and a variety of birds, many of them members of rare and endangered species. Like the forests, fields, and swamps of their unexpectedly inviting habitat, both the people and the animals are all radioactive. Cesium-137 is packed in their muscles and strontium-90 in their bones. But quite astonishingly, they are also thriving. If fears of the Apocalypse and a lifeless, barren radioactive future have been constant companions of the nuclear age, Chernobyl now shows us a different view of the future. A vivid blend of reportage, popular science, and illuminating encounters that explode the myths of Chernobyl with facts that are at once beautiful and horrible, Wormwood Forest brings a remarkable land - and its people and animals - to life to tell a unique story of science, surprise and suspense.
Keywords: Explore Science; Environment and Environmental Studies

The Language of Life: How Cells Communicate in Health and Disease - Debra Niehoff (The National Academies Press, 2005)
Cooperation requires conversation. Human beings speak to one another. Sounds, scents, and postures allow animals to make their point. While individual cells can’t talk, hiss, growl, or bare their teeth, they nevertheless communicate regularly. Their language is based not on words or gestures, but on chemistry —using molecules where we would use words, constructing sentences from chains of proteins. The cells that make up the bodies of muticellular organisms inform, wheedle, command, exhort, reassure, nurture, criticize, and instruct each other to direct every physiological function, report every newsworthy event, record every memory, heal every wound. And each of those chemical conversations represents an opportunity for scientists and physicians. The molecular biologists who worked for over a decade to sequence the human genome have sometimes referred to that sequence as the “book of life.” To our cells, that “book” is no more than a dictionary—only living cells can converse, forming the network that allows our 60 trillion cells to function as a single organism. For nearly a century, researchers have been straining to hear the whispered conversations among cells, hoping to master the basics of their language. They know that if we can decipher and translate this cellular chatter, we have the potential for sending signals of our own that could repair wounds, reduce cholesterol, control insulin levels, or even block the reproduction of cancer cells. The possibilities are as endless as they are intriguing. The Language of Life is a fantastic story of discovery, blending the vision of science with the poetry of life itself.
Keywords: Biology and Life Sciences; Health and Medicine

Memory: The Key to Consciousness - Richard F. Thompson; Stephen A. Madigan (The National Academies Press, 2005)
Memory is perhaps the most extraordinary phenomenon in the natural world. Every person’s brain holds literally millions of bits of information in long-term storage. This vast memory store includes our extensive vocabulary and knowledge of language; the tremendous and unique variety of facts we’ve amassed; all the skills we’ve learned, from walking and talking to musical and athletic performance; many of the emotions we feel; and the continuous sensations, feelings, and understandings of the world we term “consciousness.” And we routinely access this tremendous volume of data in the blink of an eye. Without memory there can be no mind as we understand it. Focusing on cutting edge research in behavioral and neuroscience, Memory, the second title in the Science Essentials series, is a primer of our current scientific understanding of the mechanics of memory and learning. During the past two decades, memory research has accelerated and we have seen an explosion of new knowledge about the brain. For example, there now exists a wide-ranging and successful applied science devoted specifically and exclusively to the study of memory that has yielded better procedures for eliciting valid recollections in legal settings and improved our track record for diagnosing and treating memory disorders. Everyone fascinated by the cutting-edge scientific research that is revealing the incredible scope and power of the human brain will find this to be an unforgettable book.
Keywords: Biology and Life Sciences

Flash Flood Forecasting Over Complex Terrain: With an Assessment of the Sulphur Mountain NEXRAD in Southern California - National Research Council (The National Academies Press, 2005)
The nation's network of more than 130 Next Generation Radars (NEXRADs) is used to detect wind and precipitation to help National Weather Service forecasters monitor and predict flash floods and other storms. This book assesses the performance of the Sulphur Mountain NEXRAD in Southern California, which has been scrutinized for its ability to detect precipitation in the atmosphere below 6000 feet. The book finds that the Sulphur Mountain NEXRAD provides crucial coverage of the lower atmosphere and is appropriately situated to assist the Los Angeles-Oxnard National Weather Service Forecast Office in successfully forecasting and warning of flash floods. The book concludes that, in general, NEXRAD technology is effective in mountainous terrain but can be improved.
Keywords: Earth Sciences

Halley's Quest: A Selfless Genius and His Troubled Paramore - Julie Wakefield (The National Academies Press, 2005)
For most people, Edmond Halley is best known for accurately predicting the periodic appearance of the comet that ultimately would bear his name. But his greatest achievement may have been overlooked— indeed few people know that it was Halley who solved the riddle of accurate navigation for all sea-going vessels. As seventeenth-century scientists gradually came to believe that the inside of the Earth was magnetized they were puzzled by the fact magnetic north not only varied slightly from place to place, but gradually changed over time, suggesting a slow variation of the Earth's magnetic field. But if the Earth was permanently magnetized, how could its magnetism vary? Edmond Halley, Britain's Astronomer Royal, ingeniously proposed that the Earth contained a number of spherical shells, one inside the other, each magnetized differently, each slowly rotating in relation to the others. This brilliant deduction earned Halley the command of a small sailing ship, the 52-foot Paramore, and with it, a royal mandate. Halley was to sail forth “to stand so far into the South, till you discover the Coast of the Terra Incognita.” But more importantly, determine the variation between true and magnetic north in order to more accurately calculate longitude—a feat that would improve Britain's navigational skills and ensure its dominance of the high seas. Halley's Quest takes readers on a trilogy of sea voyages, each of which proved to be as novel and revealing as it was difficult and controversial. But more than a yarn of risk and adventure, the story at the core of the book is a deeply personal and intellectual tale that captures the science and the spirit of an almost forgotten episode in the history of navigation. Once branded a heretic by the Church and denied a prestigious scholarly chair at Oxford University, Halley ultimately changed the course of science, producing charts that described more accurate ways to navigate and documenting new geophysical phenomena ranging from ocean patterns to the motion of Jupiter's moons. This delightful book emphasizes the drama of Halley's mission and the passion of an era hungry for the stories science had to tell.
Keywords: Explore Science; Biography and Autobiography

Use of Event Data Recorder (EDR) Technology for Highway Crash Data Analysis - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2005)
TRB’s National Cooperative Highway Research Program (NCHRP) Research Results Digest 298: Use of Event Data Recorder (EDR) Technology for Highway Crash Data Analysis examines the benefits and the costs of using EDR data in highway crash data analysis and research. The report also summarizes the final report of NCHRP Project 17-24 that is available as NCHRP Web-Only Document 75. Web-Only Document 75 examines recommendations for the enhancement of EDRs to meet the specific needs of highway crash data analysis and includes recommended EDR database format for agencies that seek to collect and systematically store EDR data.
Keywords: Transportation and Infrastructure

Fed Up!: Winning the War Against Childhood Obesity - Susan Okie (The National Academies Press, 2005)
Once dismissed by the medical profession as a purely cosmetic problem, obesity now ranks second only to smoking as a wholly preventable cause of death. Indeed, it's implicated in 300,000 deaths each year and is a major contributor to heart disease, diabetes, high blood pressure, high cholesterol, and depression. Even conservative estimates show that 15% of all children are now considered to be overweight--worldwide there are 22 million kids under five years old that are defined as fat. Supersized portions, unhealthy diets, and too little physical activity certainly contribute to what's making kids 'fat.' But that's not the whole story. Researchers are at a loss to explain why obesity rates have risen so suddenly and so steeply in the closing decades of the 20th century. But head out to the beaches, playgrounds, and amusement parks, and it's obvious that overweight children are more numerous and conspicuous. We see it in our neighborhoods and we read it in the headlines. Our nation--indeed the world--is in crisis. But knowledge is power and it's time to arm ourselves in the battle to win the war on obesity. Fed Up! is just what the doctor ordered. Based in part on the Institute of Medicine's ground-breaking report on childhood obesity, this new book from family physician and journalist Susan Okie provides in-depth background on the issue; shares heartrending but instructive case studies that illustrate just how serious and widespread the problem is; and gives honest, authoritative, science-based advice that constitute our best weapons in this critical battle.
Keywords: Health and Medicine

The Threat of Pandemic Influenza: Are We Ready? Workshop Summary - Institute of Medicine (The National Academies Press, 2005)
Public health officials and organizations around the world remain on high alert because of increasing concerns about the prospect of an influenza pandemic, which many experts believe to be inevitable. Moreover, recent problems with the availability and strain-specificity of vaccine for annual flu epidemics in some countries and the rise of pandemic strains of avian flu in disparate geographic regions have alarmed experts about the world's ability to prevent or contain a human pandemic. The workshop summary, The Threat of Pandemic Influenza: Are We Ready? addresses these urgent concerns. The report describes what steps the United States and other countries have taken thus far to prepare for the next outbreak of "killer flu." It also looks at gaps in readiness, including hospitals' inability to absorb a surge of patients and many nations' incapacity to monitor and detect flu outbreaks. The report points to the need for international agreements to share flu vaccine and antiviral stockpiles to ensure that the 88 percent of nations that cannot manufacture or stockpile these products have access to them. It chronicles the toll of the H5N1 strain of avian flu currently circulating among poultry in many parts of Asia, which now accounts for the culling of millions of birds and the death of at least 50 persons. And it compares the costs of preparations with the costs of illness and death that could arise during an outbreak.
Keywords: Health and Medicine

Space Studies Board Annual Report 2004 (The National Academies Press, 2005)